WLS inhibits melanoma cell proliferation through the β-catenin signalling pathway and induces spontaneous metastasis - Yang, Pei-Tzu; Anastas, Jamie N.; Toroni, Rachel A.; Shinohara, Michi M.; Goodson, Jamie M.; Bosserhoff, Anja K.; Chien, Andy J.; Moon, Randall T. (Embo Molecular Medicine, 2012)
Elevated levels of nuclear β-catenin are associated with higher rates of survival in patients with melanoma, raising questions as to how ß-catenin is regulated in this context. In the present study, we investigated the formal possibility that the secretion of WNT ligands that stabilize ß-catenin may be regulated in melanoma and thus contributes to differences in ß-catenin levels. We find that WLS, a conserved transmembrane protein necessary for WNT secretion, is decreased in both melanoma cell lines and in patient tumours relative to skin and to benign nevi. Unexpectedly, reducing endogenous WLS with shRNAs in human melanoma cell lines promotes spontaneous lung metastasis in xenografts in mice and promotes cell proliferation in vitro. Conversely, overexpression of WLS inhibits cell proliferation in vitro. Activating β-catenin downstream of WNT secretion blocks the increased cell migration and proliferation observed in the presence of WLS shRNAs, while inhibiting WNT signalling rescues the growth defects induced by excess WLS. These data suggest that WLS functions as a negative regulator of melanoma proliferation and spontaneous metastasis by activating WNT/β-catenin signalling. Even though WNT/β-catenin signaling is downregulated, malignant melanomas express high levels of WNT ligands. Here, the authors show that reduced expression of the WNT secretory receptor WLS could be the cause of loss of WNT/β-catenin signaling. © 2012 The Authors. Published by John Wiley and Sons, Ltd on behalf of EMBO.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Beta-catenin; Melanoma; Spontaneous metastasis; WNT secretion; WNTLESS